Adaptation and conservation insights from the koala genome - Chong, AYY; Johnson, RN; O’Meally, D; Chen, Z; Etherington, GJ; Ho, SYW; Nash, WJ; Grueber, CE; Cheng, Y; Whittington, CM; Dennison, S; Peel, E; et al. (Springer Nature, 2018)
The koala, the only extant species of the marsupial family Phascolarctidae, is classified as ‘vulnerable’ due to habitat loss and widespread disease. We sequenced the koala genome, producing a complete and contiguous marsupial reference genome, including centromeres. We reveal that the koala’s ability to detoxify eucalypt foliage may be due to expansions within a cytochrome P450 gene family, and its ability to smell, taste and moderate ingestion of plant secondary metabolites may be due to expansions in the vomeronasal and taste receptors. We characterized novel lactation proteins that protect young in the pouch and annotated immune genes important for response to chlamydial disease. Historical demography showed a substantial population crash coincident with the decline of Australian megafauna, while contemporary populations had biogeographic boundaries and increased inbreeding in populations affected by historic translocations. We identified genetically diverse populations that require habitat corridors and instituting of translocation programs to aid the koala’s survival in the wild.